Dari Klausul ‘Menguntungkan Korporasi’ ke Pertanggungjawaban Pidana: Analisis Yuridis Pertanggungjawaban Korporasi dalam Tindak Pidana Korupsi - Jurais M. Saleh (ALADALAH: Jurnal Politik, Sosial, Hukum dan Humaniora, 2025)
The corruption cases involving sugar importation in Indonesia reveal the role of corporations as beneficiaries of abuses of power that cause state financial losses. This condition highlights the necessity of re-examining the legal construction of corporate criminal liability, particularly the relevance of the “corporate benefit” clause as a basis for prosecution. The research applies a normative juridical approach supported by empirical analysis of relevant court decisions. Findings indicate that the clause serves as a preliminary indicator of corporate fault, linking individual actions to corporate interests. The application of identification, vicarious liability, and aggregation theories reinforces the legal foundation for holding corporations criminally liable when proven to have gained from acts of corruption. Ensuring consistent enforcement of these legal principles is essential to advancing justice and enhancing the effectiveness of anti-corruption efforts in Indonesia.